SIFAT VENIR DAN KAYU LAPIS 7 JENIS KAYU DARI MALUKU - M I Iskandar; Suwandi Kliwon; Paribotro Sutigno (Jurnal Penelitian Hasil Hutan, 1987)
The characteristics studied  are peeling properties,  physical  properties  of  the veneer, gluing properties  and some physical  and  mechanical properties  of  the plywood   (both  triplex and multiplex).All logs from the 7 wood species could be peeled satisfactorily  in cold condition.   Veneer of  0.9 mm and 1.5  mm thickness  could be produced at a cutting  angle between  91°-93°.Average shrinkage  of  the veneer is 7%.  Average swelling from oven dry condition  is 3%.Water resistant,  bonding  strength  for all wood  species studied  meet Indonesian,   Japanese  and German standards. Average thickness reduction due to pressing in the plywood   manufacturing  process  is 0.15 mm.Specific  gravity  of  the plywood   is about  6 percent  higher than that  of  the wood from   which it is made  of